Realization Of 3-D Reflectors By Using Metal-Air And Semiconductor-Air Based Photonic Structures At Three Communication Windows - et. al., Sakti Prasan Mohanty, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study is based on analysis of three dimensional photonic crystal(PhC) to envisage a photonic reflector pertaining to suitable optical communication wavelengths (850/1310/1550nm). The said photonic reflector application is envisaged separately by two 3D PCSs, which comprised of semiconductor (germanium) and metal (iron) based circular rods respectively, arranged on a square lattice having air as the background material. A detailed assay of photonic band gap is the cornerstone of this work, which is studied through manipulating the plane wave expansion (PWE) technique. PBG is meticulously controlled by suitably selecting the geometrical parameters like refractive index of the background material, height of the structure, lattice constant andradius of the rods. Simulation outcomes explored that semiconductor based PhC reflects 850nm, 1310nm and 1550nm by selecting diameter of the circular rods as 282 nm, 608 nm and 771 nm respectively, whereas metal based PCS reflects the aforementioned wavelengths for diameter of the circular rods as 335 nm, 1070 nm and 871 nm respectively. Further, we investigated the variation in reflected wavelength for change in the diameter of the circular barsin both the proposed structures. Thus, the proposed optical reflectors open up an avenue for wide range of applications vis-à-vis three communication windows.